Pembrolizumab for previously treated advanced anal squamous cell carcinoma: results from the non-randomised, multicohort, multicentre, phase 2 KEYNOTE-158 study. (May 2022) - Marabelle, Aurelien; Cassier, Philippe A; Fakih, Marwan; Kao, Steven; Nielsen, Dorte; Italiano, Antoine; Guren, Tormod Kyrre; van Dongen, Marloes G J; Spencer, Kristen; Bariani, Giovanni Mendonca; Ascierto, Paolo A; Santoro, Armando; et al.
Summary: Background: Outcomes in advanced anal squamous cell carcinoma are poor, with few treatment options and controlled clinical trials. We evaluated the efficacy and safety of pembrolizumab in patients with advanced anal squamous cell carcinoma (cohort A) from the phase 2 KEYNOTE-158 study. Methods: Eligible patients enrolled in the ongoing non-randomised, multicohort, multicentre, phase 2 KEYNOTE-158 study, which was done across 38 centres worldwide, were aged 18 years or older; had histologically or cytologically confirmed advanced or metastatic anal squamous cell carcinoma; had previous failure of or intolerance to standard therapy or no standard therapy options; and had a PD-L1-evaluable tissue sample. Patients received pembrolizumab 200 mg intravenously every 3 weeks for 2 years, or until disease progression, unacceptable toxicity, investigator's decision to withdraw the patient from the study, or withdrawal of patient consent. The primary endpoint was objective response, as assessed by Response Evaluation Criteria in Solid Tumors version 1.1. Efficacy and safety analyses included all patients who received at least one dose of pembrolizumab. The trial is registered with ClinicalTrials.gov, NCT02628067 . Findings: Between March 3, 2016, and July 23, 2018, 163 patients were screened, of whom 112 were enrolled and treated in the anal cancer cohort. 91 (81%) patients were female, 104 (93%) had M1 disease, and 75 (67%) had PD-L1-positive tumours. The median time from first dose to data cutoff (June 27, 2019) was 34·7 months (IQR 32·5–36·4). 12 (11%, 95% CI 6–18) patients had an objective response, including 11 (15%, 8–25) of 75 patients with PD-L1-positive tumours and one (3%; 0–17) of 30 patients with PD-L1-negative tumours. 68 (61%) patients had treatment-related adverse events (20 [18%] patients had grade 3–4 adverse events), the most common of which were fatigue (17 patients), diarrhoea (13), hypothyroidism (13), and nausea (13). Serious treatment-related adverse events occurred in 12 (11%) patients. 25 (22%) patients had immune-mediated adverse events, and one (1%) had an infusion reaction. There were no treatment-related deaths. Interpretation: Pembrolizumab monotherapy is a possible treatment option with a favourable benefit–risk ratio for patients with previously treated advanced anal squamous cell carcinoma who have no alternative satisfactory treatment options. Funding: Merck Sharp & Dohme.